Universal Primary Education Performance In Uganda:A Critical Analysis - Mutabaruka, Fredrick; Kazooba, Charles Tushabomwe (Researchjournali’s Journal of Management, 2017)
The aim of this study is a critical analysis of Universal Primary Education (UPE) performance in Uganda basing on to the attainment of the overall objectives of primary education as set in 1996. The core inclination for undertaking this research was the desire to assess the quality of UPE in Uganda derived from the understanding that sustainable development in developing communities like Uganda is hinged on the provision of quality education to her citizens. In order to attain this, a combination of research methods have been conducted particularly the questionnaire and content analysis; where 84 questionnaires were returned out of 84 sent out giving 100% response rate. Further analysis was done on content documents from the districts under study on annual education reports/statements. The findings reveal that UPE increased access from nearly 2.5 million pupils in 1996 to 8.2 million pupils in 2015. Education for girls, the disabled, and the orphans also increased from 39% in 1997 to 50% in 2015, P.6 pupils’ proficiency in numeracy and literacy in the year 2015 was 51.9% and 52.6% respectively. However, the issue of quality remains a challenge. It was recommended that government needs to go back on the drawing board re-strategise the programme and focus on the education priorities that focus on quality education and ensure satisfaction of stakeholders’ expectations.
Keywords: Universal Primary Education; Performance; Education quality; Equity in education